2021
DOI: 10.1002/oa.2982
|View full text |Cite
|
Sign up to set email alerts
|

Sacralization in the Mary Rose and Kronan assemblages: An inconsistently recorded anomaly

Abstract: This study aims to promote consistent observations of sacralization, a relatively common form of lumbosacral transitional vertebrae (LSTV). Sacralization can inform on genetic affiliation. There are four types, ranging from enlarged transverse processes to bony ankylosis. Complete sacralization reportedly occurs in 1.5%-14% of archeological and modern populations, yet clinical studies can conflate types, resulting in rates as high as 46%. Archeologically obtained sacra and lower lumbar vertebrae from two histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Moreover, lumbarization cannot reliably be distinguished from sacralization in fragmentary skeletal remains, thereby obscuring any potential functional implications caused by such anomalies. Understanding the T A B L E 1 Previously published frequencies of transitional vertebrae (TV) from clinical studies and anatomical collections (studies based on archaeological material were omitted but see Drew & Kjellström, 2021 for an overview) morphological variation, that these anomalies introduce, has important implications in both clinical and archaeological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lumbarization cannot reliably be distinguished from sacralization in fragmentary skeletal remains, thereby obscuring any potential functional implications caused by such anomalies. Understanding the T A B L E 1 Previously published frequencies of transitional vertebrae (TV) from clinical studies and anatomical collections (studies based on archaeological material were omitted but see Drew & Kjellström, 2021 for an overview) morphological variation, that these anomalies introduce, has important implications in both clinical and archaeological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is a strong relationship between sacralization and low back pain (LBP) [ 13 , 41 , 42 ]. Sacralization is not continually interrelated to LBP; it can remain symptom-free for eras [ 16 , 43 , 44 ]. The pain due to the sacralization process is usually slow onset.…”
Section: Introductionmentioning
confidence: 99%